Concomitant large renal cancer and abdominal aortic aneurysm. An original multidisciplinar approach to solve both pathologies saving residual kidney - Roberto Falabella; Saveriano Lioi; Sabrina La Falce; Franco Camillo Ponti; Giuseppe Di Fino; Vincenzo Francesco Caputo; Andrea Esposito (Urology Case Reports, 2024)
A 65-year-old male patient presented a large mass of the left kidney and a concomitant saccular abdominal aortic aneurysm (AAA) of the infrarenal aorta. Due to the particular vascularization of the right kidney in order to allow an endovascular Aneurysm Repair (EVAR), a hybrid staged repair was planned. Through a median laparotomy, a left radical nephrectomy and an ilio-renal bypass were performed, thus creating the anatomical feasibility for subsequent EVAR. Two days later the AAA was excluded by positioning of an abdominal straight stent graft. This original surgical strategy showed to be effective and reduced invasiveness of traditional approach.